BS EN 63232-1-1. Live working. Hand protective devices against the thermal Hazards of an electric arc. Part 1-1. Test methods. Method 1: Determination of the arc rating (ELIM, ATPV and/or EBT) of hand protective devices using an open arc (1st September 2021) - British Standards Institution,
No abstract available